Sytuacja na rynku pracy w Polsce w latach 2000-2007 - Knapińska, Magdalena (Situation in the Polish Labour Market From 2000 to 2007, 2009)
The aim of this paper is to present, analyze and evaluate the situation in the Polish labour market between 2000 and 2008. The analysis focuses on indexes reflecting formation of particular labour market elements, i.e. the number and structure of the population according to age, which inform about the labour resources remaining at the disposal of a particular economy. Moreover, there has been studied the number of employed persons, which pictures the labour demand, meant as actually filled labour posts. The formation of the wages level and relationships has also been analyzed, taking into account the inflation rate and regarding these wages as real categories. Finally, the unemployment phenomenon has been presented, i.e. its rate and structure of the unemployed according to their education level. The review of the economic data in the labour market has allowed to make several conclusions regarding determination of main tendencies occurring in the Polish labour market. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 145-155